Advantages of Using HJ-Biplot Analysis in Executive Functions Studies - Ruiz, Natalia Cadavid; Egido, Jaime; Galindo-Villardón, Purificación; Del-Río, Pablo (Psicologia: Teoria e Pesquisa, 2019)
Executive functions (EFs) are considered a multiple system of processing, associated with different components, such as inhibition, working memory, planning, among others. The study of EFs requires the assessment of all its components, having in mind the socio-demographic and cognitive characteristics of the target population. Nowadays, analysis of variance is used to achieve this goal; nevertheless, HJ-Biplot analysis overcome its limitations by allowing simultaneous examination of multiple data, such as those generated in EFs studies. This study evaluates possible differences in the EFs of 80 8”“year-old Colombian children by their sex, socio-economic status and type of school they attend, to exemplify the advantages of using HJ-Biplot analysis in neuropsychological studies.